A super-hydrophobic composite membrane for high-throughput and anti-wetting membrane distillation based on CNTs, preparation method and use thereof

By using a superhydrophobic composite membrane based on CNTs in membrane distillation technology, the problems of high operating pressure and poor wetting resistance in the existing membrane desalination technology are solved, and the synchronous improvement of high water flux and excellent wetting resistance are achieved.

CN118807501BActive Publication Date: 2025-04-04HUAIYIN TEACHERS COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411036875.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-11-08
Filing Date
2024-07-30
Publication Date
2025-04-04
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The existing membrane desalination technology has problems such as high operating pressure, high salinity, serious membrane pollution and scale, and hydrophobic membranes are difficult to maintain excellent anti-wetting properties during membrane distillation, resulting in a reduced desalination efficiency.

Method used

A superhydrophobic composite membrane based on carbon nanotubes (CNTs) was used to prepare a PVDF porous membrane by steam-induced phase separation method, and the carboxylated CNTs were loaded onto the membrane surface, and then perfluorinated treatment was performed to form a superhydrophobic composite membrane with a network structure.

Benefits of technology

It realizes the synchronous improvement of water flux and wettability during membrane distillation, enhances the hydrophobicity and soil resistance of the membrane, improves salt retention and water flux, and reduces the maximum pore size and roughness of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005034121430000071
    Figure GDA0005034121430000071
  • Figure HDA0004971330500000011
    Figure HDA0004971330500000011
  • Figure HDA0004971330500000012
    Figure HDA0004971330500000012
Patent Text Reader

Abstract

In this paper, a super-hydrophobic composite membrane based on carbon nanotubes (CNTs) was constructed to simultaneously improve the water flux and anti-wetting performance of the membrane. The composite membrane is supported by a hydrophobic polyvinylidene fluoride (PVDF) porous membrane prepared by a steam-induced phase separation method, and a super-hydrophobic CNTs layer is used as a functional composite layer. On the one hand, the high thermal conductivity of the CNTs layer reduces the temperature polarization effect, while the network-structured CNTs layer also increases the effective evaporation area, thereby synergistically enhancing the mass transfer driving force of the MD process. On the other hand, the network-structured CNTs layer significantly reduces the maximum pore size of the PVDF membrane, and the fluorination modification also reduces the surface energy of CNTs, thereby significantly improving the anti-wetting performance of the composite membrane. The super-hydrophobic composite membrane based on CNTs provides a new idea for the design and preparation of high-performance membrane materials for MD.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a CNTs-based super-hydrophobic composite membrane for high-throughput and anti-wetting membrane distillation, a preparation method and application thereof, and belongs to the technical field of separation membrane material preparation and application. Background Art

[0002] Conventional desalination technologies can be divided into two categories: thermal and membrane. Thermal methods mainly include multi-stage flash evaporation and multi-effect evaporation. Although thermal desalination technology is mature, its energy consumption and operating costs are high, making it difficult to popularize and apply. Membrane method, that is, membrane separation technology, is currently the mainstream membrane desalination technology, mainly reverse osmosis. However, this technology has problems such as high operating pressure, great influence of salinity, severe membrane pollution and scaling. Membrane distillation (MD), as an emerging desalination technology that combines membrane separation technology with distillation process, has attracted great attention in recent years due to its advantages such as high retention rate, insensitivity to salt concentration, and ability to utilize low-grade thermal energy. MD technology uses a hydrophobic microporous membrane as the medium. The volatile components in the feed liquid pass through the membrane pores in the form of steam under the action of the transmembrane vapor pressure difference, while other non-volatile components are retained in the feed liquid, thereby achieving the purpose of product separation and purification.

[0003] High water flux and excellent anti-wetting properties are two important challenges for the practical application of MD technology in high-salinity wastewater treatment. On the one hand, a hydrophobic membrane with high water flux means high treatment efficiency. According to Darcy's law, the transmembrane flux (J) is proportional to the vapor partial pressure difference (ΔP) of the volatile components on both sides of the hydrophobic membrane (i.e., J=KΔP). Among them, the transmembrane mass transfer coefficient (K) is only related to the properties of the porous membrane itself (such as pore size, porosity, tortuosity factor, membrane thickness, etc.), and has nothing to do with the operating conditions. Optimizing the structural parameters of the hydrophobic membrane is the basic method to increase the water flux, which mainly includes increasing the pore size or porosity of the membrane, reducing the membrane thickness, and reducing the tortuosity of the membrane pores. On the other hand, the most important function of the hydrophobic membrane in the MD process is to separate the liquids on the feed side and the permeate side, and only allow volatile substances to pass through the membrane pores in the form of gas. Therefore, the excellent anti-wetting performance of the hydrophobic membrane is a key factor for the successful implementation of the MD process. Once the membrane pores are wetted, the gas in the membrane pores will be replaced by liquid, and the salt solution on the feed side can freely enter the permeate side through the wetted membrane pores, resulting in reduced desalination efficiency and failure of the MD process. At present, the main evaluation index of the anti-wetting property of hydrophobic membranes is the liquid entry pressure (LEP, which can be expressed by the formula LEP = -2βγ1cosθ / r max The LEP value is the minimum static pressure required for the liquid to enter the membrane pores. Obviously, the larger the LEP value of the membrane, the stronger its anti-wetting performance. From the LEP formula, it can be seen that it is related to the geometric coefficient of the membrane pores (β), the surface tension of the liquid (γ l ), the static contact angle (CA) of the liquid on the membrane surface (θ) and the maximum pore radius (r max). For membrane pore structure and pore size, regular pore structure and smaller pore size will increase the LEP value. For static CA (related to membrane hydrophobicity), high CA, that is, an increase in the surface roughness of the hydrophobic membrane or a further decrease in the surface energy can increase the LEP value of the membrane. In order to overcome the membrane wetting phenomenon, researchers have conducted extensive explorations from the perspective of surface lyophobicity. So far, a variety of methods have been developed to prepare superhydrophobic and amphiphobic membranes.

[0004] During the MD process, it is crucial to maintain the lyophobicity of the membrane, but increasing the lyophobicity of the membrane surface usually leads to a decrease in water flux. Chiao et al. prepared a perfluorosilane-modified fully hydrophobic nanofibrous polyvinylidene fluoride (PVDF) membrane, whose water flux (16LMH) was lower than that of the original PVDF membrane (20LMH), but the former showed better anti-wetting properties than the latter. Fang et al. prepared a fully hydrophobic membrane with a corrugated structure through a series of steps including electrospinning, hot pressing, physical compression embossing, and perfluorinated coating. Compared with 20.8 and 21.5LMH of unpatterned PVDF membrane and patterned PVDF membrane, the water flux of the perfluoroalkyl modified membrane was slightly lower, 18.0 and 17.9LMH, respectively. Deka et al. combined electrospinning and electrospraying to prepare a double-layer superhydrophobic electrospun nanofibrous membrane with high anti-wetting and anti-fouling functions, whose initial water flux was reduced from 24.3LMH of the electrospun nanofibrous membrane without nanoparticles to 22.7LMH, but showed higher anti-wetting performance. Previous studies have shown that membranes with lower anti-wetting properties (still waterproof) allow the liquid-air interface to penetrate deeper into the membrane compared to membranes with higher wettability, resulting in a larger liquid-air contact area and a larger water flux. In summary, for membranes with the same surface morphology but different anti-wetting properties, there is often a trade-off between water flux and anti-wetting properties. Summary of the invention

[0005] The present invention proposes a super-hydrophobic composite membrane based on carbon nanotubes (CNTs) to simultaneously improve the water flux and anti-wetting property of the MD process. A PVDF porous membrane prepared by the vapor-induced phase separation (VIPS) method is used as a carrier of the composite membrane. Subsequently, CNTs are loaded onto the surface of the PVDF porous membrane by vacuum filtration to obtain a composite layer with a network structure. Finally, a perfluorinated substance is covalently grafted onto the surface of the CNTs to obtain a super-hydrophobic composite membrane. The morphology, pore size distribution, wettability, water flux and stability of the membrane are systematically characterized. The composite membrane constructed by coupling an optimized CNTs layer with a network structure with a PVDF porous support with a macroporous structure exhibits excellent anti-wetting and water flux in the MD process. This work studies the strengthening theory of the CNTs layer on the water flux and anti-wetting property of the composite membrane, which will provide ideas for the development of high-performance hydrophobic membrane materials for the MD process.

[0006] A high-throughput and anti-wetting super-hydrophobic composite membrane for membrane distillation based on CNTs comprises a porous base membrane and a supporting layer supported on the surface of the porous base membrane. The supporting layer is mainly composed of carboxyl carbon nanotubes, and the surface of the carboxyl carbon nanotubes is modified with perfluoropolyamine.

[0007] The super-hydrophobic composite film has a water drop contact angle of 130-170°.

[0008] The method for preparing the above-mentioned CNTs-based high-throughput and anti-wetting super-hydrophobic composite membrane for membrane distillation comprises the following steps:

[0009] Step 1, obtaining a porous base membrane;

[0010] Step 2, dispersing the carboxylated carbon nanotubes in a solution to obtain a suspension;

[0011] Step 3, the suspension is filtered to load the carboxylated carbon nanotubes onto the surface of the porous base membrane, and after drying, fluorination is performed to obtain a super-hydrophobic composite membrane.

[0012] The fluorination process includes:

[0013] Step a, preparing a fluorine-containing polyamine;

[0014] Step b, immersing the porous base membrane loaded with carbon nanotubes in an activation reaction solution to activate the surface carboxyl groups, then adding fluorine-containing polyamine to carry out a grafting reaction, and then washing and drying.

[0015] The activation reaction solution refers to an ethanol solution of EDC·HCl and NHS, and the concentrations of EDC·HCl, NHS and fluorinated polyamine in the activation reaction solution are 0.1-0.5 mol / L, 0.05-0.30 mol / L, and 0.05-0.30 mol / L, respectively; the grafting reaction conditions are 5-40° C. for 10-30 hours.

[0016] The preparation process of the fluorine-containing polyamine comprises: adding EDC·HCl, NHS and PFOA into an organic solvent, activating for a certain period of time, then adding EDA to react, filtering and washing the product to obtain the fluorine-containing polyamine.

[0017] The molar ratio of EDC·HCI, NHS, PFOA and EDA is: 2:0.5-1.5:0.5-1.5:1-3; the organic solvent is ethanol; the reaction is carried out at 5-40°C for 10-30h.

[0018] The porous base membrane is a PVDF membrane, which is prepared by the VIPS method.

[0019] The surface loading of the above-mentioned carboxylated carbon nanotubes on the porous substrate is 0.1-10 mg / cm 2 .

[0020] The pore size range of the superhydrophobic composite membrane is 300-5nm, and the maximum pore size range is 20-400nm.

[0021] The above-mentioned super-hydrophobic composite membrane is used in membrane distillation dehydration.

[0022] A method for reducing the roughness of a membrane and / or reducing the maximum pore size of a membrane, comprising the following steps:

[0023] Step 1, obtaining a porous base membrane; Step 2, dispersing carboxylated carbon nanotubes in a solution to obtain a suspension; Step 3, filtering the suspension to load the carboxylated carbon nanotubes on the surface of the porous base membrane, drying the suspension, and then fluorinating the suspension to obtain a super-hydrophobic composite membrane;

[0024] In the step of reducing the roughness, the loading amount of carboxylated carbon nanotubes on the surface of the porous substrate is 0.66 mg / cm 2 In the step of reducing the maximum pore size of the membrane, the surface loading of the carboxylated carbon nanotubes on the porous base membrane is 0.1-10 mg / cm 2 .

[0025] Beneficial Effects

[0026] The present invention has successfully developed a super-hydrophobic composite membrane based on CNTs, which can simultaneously improve the water flux and anti-wetting performance of the membrane during MD. The network structure CNTs functional layer of the composite membrane has comprehensive advantages such as good thermal conductivity, large specific surface area, super-hydrophobicity, and small maximum pore size. The specific advantages include:

[0027] (1) Due to the loading of CNTs, the membrane surface morphology has changed significantly. SEM images show that the large pores formed by the spherical particle structure on the original membrane surface are covered by the small pores formed by the CNTs network structure, and the membrane pore size decreases significantly with the increase of the loading amount.

[0028] (2) After loading carboxylated CNTs, the hydrophilicity of the membrane surface increases, and the water contact angle decreases with the increase of the loading amount. As expected, the surface energy of the composite membrane decreases after perfluorinated treatment, which significantly increases the hydrophobicity of the membrane surface, and the contact angle of the composite membrane increases with the increase of CNTs loading. Even when the CNTs loading amount is as low as 0.22 mg / cm 2 , the surface of the fully fluorinated composite membrane can still achieve a super-hydrophobic effect (>150°).

[0029] (3) The effect of CNTs loading on MD performance was studied by DCMD test. The results showed that the water flux increased first and then decreased with the increase of CNTs loading. 2 When , the water flux reached the highest value, which increased by 21.8% compared with the original membrane.

[0030] (4) A mixed solution of 35 g / L NaCl and gradient concentrations of SDBS was used as the feed solution for the DCMD test. The results showed that the composite membrane could still maintain a stable water flux and a higher salt rejection rate at a higher concentration of SDBS compared with the original membrane, indicating that it has excellent anti-wetting properties. This study provides a feasible solution for the design and preparation of CNTs-based composite membranes for efficient MD processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 :Schematic diagram of preparation of super hydrophobic composite membrane

[0032] Figure 2 : Dispersion of CNTs in different solvents: (a) water; (b) a mixed solution of isopropanol and water with a volume ratio of 7:4

[0033] Figure 3 Digital photos and corresponding SEM images of membranes with different CNTs-COOH loadings ((a)-(f) correspond to 0, 0.22, 0.55, 0.66, 0.88, and 3.3 mg / cm, respectively). 2 ), as well as AFM height images (g) and roughness (h) of the original and composite films (corresponding to CNTs-COOH contents of 0 and 0.66 mg / cm, respectively 2 ), (i) CNTs-COOH loading at different magnifications is 0.66 mg / cm 2 SEM image of the cross section of the composite film.

[0034] Figure 4 : (a) ATR-FTIR spectra of PVDF membrane, PVDF@0.66CNTs membrane and PVDF@0.66CNTs-PFOA membrane, (b) high-resolution XPS spectrum of PVDF membrane (c) high-resolution XPS spectrum of PVDF@0.66CNTs-COOH membrane, (d) high-resolution XPS spectrum of PVDF@0.66CNTs-PFOA membrane.

[0035] Figure 5: (a) Comparison of WCA of membranes with different CNTs-COOH loadings before and after perfluorination, (b) WCA and SA values ​​of PVDF, PVDF@0.66CNTs-COOH, and PVDF@0.66CNTs-PFOA membranes. (c) Snapshots of water droplets during WCA measurements of pristine PVDF, PVDF@0.66CNTs-PFOA, and PVDF@2.2CNTs-PFOA membranes. (d) Wetting behavior of water on the surface of superhydrophobic CNTs layer with network structure (Cassie-Baxter model).

[0036] Figure 6 :(a) Effect of CNTs-COOH loading on the average pore size, maximum pore size and porosity of the membrane, (b) water vapor flux and salt retention performance of different membranes (using 35 g / L NaCl solution as feed), (c) LEP values ​​of different membranes.

[0037] Figure 7 : (a) Contact angles of membranes with different CNTs-COOH loadings for liquids with different surface tensions, (b) Water flux and salt rejection performance of the membranes using 35 g / L NaCl solutions with different SDBS concentrations as feed.

[0038] Figure 8 : (a) Water vapor flux, (b) conductivity as a function of water recovery in gypsum scaling experiments (the initial volume of 1000 mL of feed consisted of 60 mM NaCl, 14.8 mM CaCl2 and 14.8 mM Na2SO4) (c) scaling on membrane surfaces with different characteristics, (d) schematic diagram of the wetting state of membrane surfaces with different characteristics.

[0039] Fig. 9 : Schematic diagram of membrane cross-section. (a) Original PVDF membrane, (b) composite membrane with appropriate CNTs loading, (c) composite membrane with excessive CNTs loading. (d) Original PVDF membrane in DCMD, (e) Schematic diagram of mass transfer and heat transfer process of composite membrane. DETAILED DESCRIPTION

[0040] In membrane distillation (MD), improving membrane hydrophobicity is crucial to improving its anti-wetting performance, but the increase in membrane hydrophobicity usually leads to a decrease in water flux. In this paper, a superhydrophobic composite membrane based on carbon nanotubes (CNTs) was constructed to simultaneously improve the water flux and anti-wetting performance of the membrane. The composite membrane is supported by a hydrophobic polyvinylidene fluoride (PVDF) porous membrane prepared by steam-induced phase separation, and a superhydrophobic CNTs layer is used as a functional composite layer. On the one hand, the high thermal conductivity of the CNTs layer reduces the temperature polarization effect, and the network-structured CNTs layer also increases the effective evaporation area, thereby synergistically enhancing the mass transfer driving force of the MD process. On the other hand, the network-structured CNTs layer significantly reduces the maximum pore size of the PVDF membrane, and the fluorination modification also reduces the surface energy of the CNTs, thereby significantly improving the anti-wetting performance of the composite membrane. When treating 35 g / L brine, the water flux of the composite membrane increased from 20.0 LMH of the original PVDF membrane to 24.4 LMH, and the salt rejection rate exceeded 99.9%. More importantly, when treating 35 g / L high-salinity water containing 1.0 mM sodium dodecylbenzene sulfonate, the water flux and salt rejection of the PVDF membrane dropped rapidly, while the water flux of the composite membrane remained stable (about 23 LMH) during the test time, and the salt rejection was greater than 99.9%. The CNTs-based superhydrophobic composite membrane provides a new idea for the design and preparation of high-performance membrane materials for MD.

[0041] Materials and Chemicals

[0042] PVDF resin( K-761, molecular weight = 440000Da) was purchased from Elf Atochem. CNTs-COOH (inner diameter 5-12nm, outer diameter 30-50nm, length 10-20μm), N,N-dimethylformamide (DMF, 98%), 1,2-propylene glycol (PG, 98%), ethylenediamine (EDA, 99%), perfluorooctanoic acid (PFOA, 96%), 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl, 98%), and N-hydroxysuccinimide (NHS, 98%); sodium dodecylbenzenesulfonate (SDBS, 95%), sodium chloride (≥96.0%), isopropanol (≥99.7%), and anhydrous ethanol (≥99.5%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (China). All chemicals were used directly in the experiments without further purification. The nonwoven fabric (TA3631) used as a carrier was provided by Shanghai Tianle Textile New Materials Co., Ltd. Deionized (DI) water was obtained from a Milli-Q ultrapure water system (Millipore, USA).

[0043] Example 1 Preparation of super hydrophobic composite membrane

[0044] Preparation of PVDF porous membrane. The PVDF porous membrane was prepared by the VIPS method. Specifically, PVDF was first added to a mixture of DMF and PG to prepare a casting solution, and mechanically stirred at 80°C until uniform. The polymer solution was then placed in an oil bath at 80°C for 4 hours to remove bubbles. The casting solution was then evenly scraped onto a non-woven fabric fixed on a glass plate using a scraper with a wet film thickness of 250 μm. The nascent membrane was transferred to a constant temperature and humidity chamber (T = 60°C, relative humidity = 85%) for 1 minute, then immediately taken out and placed in a room temperature water bath to thoroughly complete the phase inversion process.

[0045] Loading of CNTs. Under the action of ultrasound with a power of 200 W, a certain amount of carboxylated CNTs was uniformly dispersed in a mixed solvent of water and isopropanol with a volume ratio of 4:7 for 6 hours. Then, different amounts of carboxylated CNTs (concentration of 0.1 g / L) were loaded onto the surface of the PVDF porous support layer by vacuum filtration. Finally, the membrane was placed in an oven at 50 ° C and dried for 12 hours. The composite membrane was named PVDF@xCNTs, where x represents the loading amount of CNTs, mg / cm 2 .

[0046] The steps of fluorination treatment are:

[0047] Preparation of fluorinated diamine: Add EDC·HCl (3.91g, 20mmol) and NHS (1.17g, 10mmol) to a 500mL conical flask, then add 50mL of anhydrous ethanol to completely dissolve it, then add perfluorooctanoic acid (PFOA) (4.60g, 10mmol), activate it for 15min, add ethylenediamine (1.36mL, 20mmol), and stir it magnetically at room temperature for 24h. After the reaction, place the reaction solution in a refrigerator overnight, filter to remove the byproduct urea insoluble in ethanol; then rotary evaporate to remove the solvent ethanol; then centrifuge and wash it with sodium hydroxide aqueous solution at pH=10 for 3 times, and then centrifuge and wash it with deionized water to remove the unreacted monomers perfluorooctanoic acid and ethylenediamine, as well as the dehydrating agent EDC and the activating agent NHS; finally dry to constant weight to obtain a fluorinated polyamine product.

[0048] Perfluorinated modification of CNTs surface. The dried PVDF@mCNTs membrane was soaked in an ethanol solution containing EDC·HCl (0.2 mol / L) and NHS (0.1 mol / L) for 20 min to activate the carboxyl groups on the surface of mCNTs, and then the pre-prepared fluorinated diamine (0.1 mol / L) was added and magnetically stirred until uniform. The reaction was stirred magnetically for 24 h at room temperature. After the reaction, it was soaked and washed with ethanol and DI water in turn to remove the membrane surfactant and unreacted fluorinated diamine. Finally, the membrane was placed in a 50°C oven and dried completely to obtain a superhydrophobic modified composite membrane, which was recorded as PVDF@mCNTs-PFOA membrane.

[0049] The test methods used in the following test process include:

[0050] The morphology of the membrane was observed using a field emission scanning electron microscope (FE-SEM) (Quanta 450FEG, FEI, USA). The roughness of the membrane was measured by an atomic force microscope (AFM) (NT MDT Prima). The static water contact angle (WCA) of the membrane was evaluated by a contact angle goniometer (Kino SL200B and Dataphysics OCA20) based on the average results of six random test points on the sample. The chemical groups and elemental composition of the membrane were characterized by Fourier transform infrared spectroscopy (FTIR, Thermo Scientific, Nicolet iS50) and X-ray photoelectron spectroscopy (XPS, BrukerAXSD8 Advance), respectively. The pore size characteristics of the membrane were measured by a gas-liquid exclusion pore size analyzer (PSDA-10, Gaoqian Functional Materials Co., Ltd.). The LEP values ​​of all membranes were measured using a homemade device. The pressure was gradually increased toward the chamber filled with deionized water above the membrane surface until the first water droplet was detected, at which time the pressure was defined as the LEP.

[0051] DCMD experimental device for membrane performance evaluation, with an effective membrane area of ​​3.4×4.5cm 2 At 450 mL min -1 A temperature difference of 40°C was maintained between the hot feed (60°C) and the cold permeate (20°C) of the lower cycle. The water flux (J) and salt rejection (R) were calculated by the following equations, respectively:

[0052]

[0053] Where A is the effective membrane area (m 2 );Δt is the sampling time (h); C f and C p are the conductivity of the solution on the feed side and the permeate side, respectively (μs / cm).

[0054] During the DCMD experiment, the membrane was fixed in a rectangular membrane cell with the functional membrane layer facing the hot feed side. 35 g / L NaCl solution or 35 g / L NaCl solution containing gradient concentrations of surfactant was used as simulated wastewater to evaluate the water flux and anti-wetting performance of the original membrane and the composite membrane.

[0055] The highly dispersed CNTs-COOH was loaded onto the surface of the PVDF porous support layer by vacuum filtration. The different loading amounts (0, 0.22, 0.55, 0.66, 0.88 and 3.3 mg / cm 2 ) of the membrane SEM images and digital photos such as Figure 3 It is obvious that after loading CNTs-COOH, the macroporous surface formed by particle stacking is covered by the small pore network structure formed by the disordered stacking of CNTs. Figure 3 The digital photo in b shows that when the CNTs loading is 0.22 mg / cm 2 When the CNTs loading increases, there are visible white spots on the surface of the composite membrane. This is because some CNTs-COOH are forced into the surface pores of the PVDF porous support layer under the action of external forces. As the CNTs loading increases, no obvious white spots can be seen in the digital photos of the composite membrane surface, which is attributed to the gradual increase in the packing density of CNTs on the surface of the PVDF porous support layer. AFM is used to characterize the roughness of the original and composite membrane surfaces, such as Figure 3 g, h. Compared with the original PVDF support layer with Ra = 113 nm and Rq = 168 nm, the roughness of the composite membrane is reduced to Ra = 64.9 nm and Rq = 86.9 nm. In addition, the CNTs-COOH loading is 0.66 mg / cm 2 SEM image of the cross section of the composite membrane ( Figure 3 i) It can be seen that some CNTs-COOH that first contacted the surface of the PVDF porous support layer would be embedded in the surface pores of the support layer, which improved the interfacial stability between the CNTs composite layer and the PVDF porous support layer.

[0056] ATR-FTIR was used to study the changes in the surface chemical properties of pristine PVDF, PVDF@0.66CNTs-COOH, and PVDF@0.66CNTs-PFOA membranes, such as Figure 4 As shown in (a). It is observed that the PVDF@0.66CNTs-COOH film has a -1 A weak peak appears at 3100-3500cm, which is attributed to the stretching vibration of C=O in the carboxyl group on the CNTs surface. -1The absorption peaks at 1204 and 1141 cm-1 are attributed to the symmetrical stretching vibrations of CF2 and CF3 in PFOA after perfluorination. -1 The absorption peak at is attributed to the formation of amide bonds during the introduction of PFOA on the surface of PVDF@0.66CNTs-PFOA membrane. The results of ATR-FTIR confirmed the successful occurrence of each reaction step. In addition, XPS was used to further characterize the surface chemical properties of the membrane, such as Figure 4 (b)-(d) are shown. The high-resolution C1s spectrum shows that the C1s spectrum of the original PVDF membrane is mainly composed of -CF2- (289.5eV) and -CH2- (285eV) groups. Due to the CNTs-COOH loading, the PVDF@CNTs-COOH membrane is mainly dominated by the C=C and CC (282.4eV) peaks of CNTs and the OC=O (288.6eV) and CO (283.5eV) characteristic peaks of the carboxyl functional groups. For the PVDF@CNTs-PFOA membrane, due to the grafting of perfluorinated groups, characteristic peaks of -CF3 (292.5eV), -(CF2)6- (290.5eV) and -CF2- (290eV) appeared in the spectrum. More importantly, due to the amide bond formed by the reaction of the carboxyl group of CNTs-COOH with the amine group at the end of the fluorinated diamine, new characteristic peaks of NC=O and CN appeared at 287.3eV and 284.1eV, respectively, which is consistent with the FTIR characterization results. Therefore, the XPS test results further prove the success of the chemical modification of the membrane surface.

[0057] The hydrophilicity / hydrophobicity of the membrane before and after modification was evaluated by WCA. Figure 5 As shown in Figure 2, the WCAs of the composite membranes decreased rapidly with the increase of CNTs-COOH loading, which was attributed to the increase of hydrophilic carboxyl content on the membrane surface. 2 The WCA of the composite membrane decreased from 139.6°±2.8° of the original PVDF membrane to 43.3°±1.1°. After perfluorinated treatment, the WCAs of the composite membrane increased significantly. 2 When the PVDF@0.22CNTs-PFOA membrane reaches 153.4°±1.5°, it shows that it has reached a superhydrophobic state. In addition, the WCA of the composite membrane after perfluorination treatment gradually increases with the increase of CNTs loading. When the loading reaches 3.3 mg / cm 2 When the PVDF@3.3CNTs-PFOA membrane is used, it can reach 167°±1.7°. This is because the increase in the carboxyl content on the surface of the composite membrane also increases the active sites for grafting perfluorinated molecules.

[0058] In addition, the slip properties of the membrane are very important for MD applications, which are usually determined by measuring the sliding angle (SA) of a water drop on the membrane surface. Due to its relatively high hydrophobicity, the SA of the pristine PVDF membrane is 45.2 ± 1.2° (see Figure 5 (b)). It can be understood that the water droplets tend to adhere to the surface of the PVDF@0.66CNTs-COOH membrane containing hydrophilic carboxyl groups, so that no sliding angle is generated. In addition, as expected, the PVDF@0.66CNTs-PFOA membrane exhibits an extremely low SA (~7°) due to its superhydrophobicity. More importantly, from the snapshot of the water droplets on the membrane surface during the WCA measurement ( Figure 5 (c) It can be seen that after the water drop in the probe contacts the surface of the PVDF porous support layer, it will remain on its surface when the probe is removed. This is attributed to the interaction force between the water drop and the support being greater than the interaction force between the water drop and the probe. For the composite membrane loaded with CNTs, as the probe moves, the water drop in the probe will leave the surface of the perfluorinated CNTs network. This is attributed to the Cassie-Baxter wetting state ( Figure 5 (d)), which results in a smaller interaction force between the water droplet and the perfluorinated CNTs network compared to the interaction force between the water droplet and the probe.

[0059] The pore structure characteristics of membranes, such as porosity, pore size, and pore size distribution, have a significant impact on their water vapor flux and anti-wetting properties. Figure 6 (a) shows the pore structure characteristics of the perfluorinated composite membrane with different CNTs-COOH loadings. It can be seen that the loadings are 0.22, 0.55, 0.66, 0.88, 1.1, 2.2 and 3.3 mg / cm 2 The average pore size of the composite membranes decreased from 325 nm of the original PVDF membrane to 240, 120, 115, 89, 66, 20, and 9 nm, respectively. In addition, the maximum pore size decreased from 380.7 nm of the original PVDF membrane to 357.5, 286.8, 210.6, 190.3, 87, 32.8, and 28 nm, respectively. This indicates that the average and maximum pore sizes of the composite membranes gradually decrease with the increase of the loading amount.

[0060] Figure 6 (b) shows the changes in water vapor flux and salt rejection performance of the membrane using 35 g / L NaCl aqueous solution as feed to test the CNTs-COOH content. It can be seen that the salt rejection rate of the membrane is higher than 99.9%. As the loading increases from 0 to 0.66 mg / cm 2 , the water vapor flux gradually increased. Compared with the 20LMH of the original membrane, the loading amounts were 0.22, 0.55 and 0.66 mg / cm 2The flux of the perfluorinated modified composite membrane was 21.7, 23.6 and 24.4 LMH, respectively, which increased by 8.5%, 18.0% and 22.0%. This is because the loading of CNTs increases the effective evaporation area, which is beneficial to improve the water flux. However, when the loading exceeds 0.66 mg / cm 2 When the water vapor flux increases, the water vapor flux decreases. This is because the increase in mass transfer resistance caused by CNTs loading leads to a decrease in water flux, which exceeds the increase in water flux associated with the increase in effective evaporation area. Therefore, there may be an optimal loading amount at which the composite membrane has the best water vapor flux.

[0061] LEP is currently one of the main indicators for evaluating the anti-wetting properties of hydrophobic membranes, which is defined as the minimum pressure required for liquid to enter the membrane pores. The LEP value of the membrane was measured using a homemade laboratory instrument. The results are shown in Figure 6 As shown in (c). The LEP values ​​of the composite membranes after perfluorination treatment are all higher than 0.22MPa of the original membranes. The LEP values ​​increase with the increase of CNTs-COOH loading. Especially when the loading exceeds 1.1mg / cm 2 When the loading amount reaches 3.3 mg / cm 2 The PVDF@3.3CNTs-PFOA membrane reached 0.8MPa, which is almost four times that of the original membrane. On the one hand, the pore size of the composite membrane gradually decreased with the increase of loading, especially when the loading exceeded 1.1mg / cm 2 When the average and maximum pore sizes of the composite membrane are less than 100 nm ( Figure 6 On the other hand, the perfluorinated treatment of the CNTs network layer also helps to increase the WCA of the composite membrane, thereby significantly improving its LEP value.

[0062] To investigate the wettability of the membranes to surfactants, the CA of the membranes to aqueous solutions containing different concentrations of SDBS was characterized. Figure 7 As can be seen from (a), the CA of the original membrane with an aqueous solution containing 1.5 mM SDBS is 105°, which is lower than the WCA of 140°. It is worth noting that the CA values ​​of the perfluorocomposite membranes with different CNTs-COOH loadings for SDBS aqueous solution and pure water are similar, all exceeding 150°, and the CA values ​​also increase slightly with the increase of loading.

[0063] In order to more intuitively demonstrate the anti-wetting properties of different membranes, we used 35g / L NaCl solution containing surfactant as feed to test their DCMD performance. It can be seen that when the concentration of SDBS reaches 1.0mmol / L, the water flux and salt rejection of the original PVDF membrane begin to decrease, indicating that part of the membrane pores have been wetted (see Figure 7(b)). This is because the hydrophobic tail of the surfactant in the feed binds to the hydrophobic membrane through hydrophobic-hydrophobic interactions, with its hydrophilic head facing the feed. This will cause the surface and pores of the membrane to become hydrophilic and wetted by the feed, resulting in a decrease in water vapor flux and salt retention. For the perfluorinated composite membrane, even when the concentration of the surfactant reaches 1.5mM, it can still maintain a stable water vapor flux and high salt retention, indicating that it has excellent moisture resistance. This is because the CNTs layer with a network structure reduces the maximum pore size of the membrane, and the low surface energy perfluorinated material grafted to the CNTs surface gives the membrane superhydrophobic properties, thereby synergistically improving the performance of the composite membrane.

[0064] Gypsum scaling is one of the main obstacles to MD technology in treating high-salinity water. It will reduce membrane permeability, cause pore wetting, and shorten the life of the membrane. Developing an effective membrane surface to inhibit gypsum scaling is crucial for the application of MD technology.

[0065] The gypsum scaling behavior of the membrane was evaluated using a brine solution with a high gypsum scaling tendency as the feed. It can be seen that the water vapor flux of the original PVDF membrane begins to decrease rapidly when the water recovery rate is greater than 10% ( Figure 8 The black dots in (a) indicate that gypsum scaling affects the transfer of water vapor. In addition, when the water recovery rate is greater than 10%, the conductivity of the liquid on the permeate side of the original PVDF membrane increases exponentially from 3 to 150 μS cm -1 , until the DCMD experiment is terminated ( Figure 8 b), indicating that membrane wetting occurs. Figure 8 As shown in (c), scale-induced wetting occurs when scale invades the larger surface pores of the original PVDF membrane, followed by the transfer of salt ions from the feed to the larger surface pores, promoting the growth of scale crystals within the membrane pores. In contrast, the water recovery of the composite membrane used in the MD process was significantly improved to 65% ( Figure 8 (a) shows the red dots. When the recovery rate is lower than 65%, the conductivity of the permeate liquid remains stable at 3 μS cm -1 ( Figure 8 The excellent anti-fouling performance of the composite membrane can be attributed to its reduced pore size and improved surface hydrophobicity ( Figure 8 (d)), which is beneficial to mitigate the effects of uniform nucleation and heterogeneous nucleation on gypsum scaling. These results indicate that the perfluorinated CNTs layer with a network structure can significantly mitigate the effect of gypsum scaling on the performance of the composite membrane during MD.

[0066] Based on the experimental results, the presence of the perfluorinated CNTs network may be beneficial in three aspects: (1) providing active sites for perfluorinated modification, (2) promoting water vapor transport properties, and (3) enhancing anti-wetting properties. The specific functions of the CNTs network are as follows: Fig. 9 As shown in the schematic diagram.

[0067] In contrast, the conventional method of direct perfluorination of the PVDF membrane surface during MD is usually detrimental to its water vapor permeability. In addition, alkaline treatment usually reduces the mechanical properties of PVDF membranes. In contrast, the presence of CNTs-COOH layer on the membrane surface provides more active sites for perfluorination modification, which helps to form a superhydrophobic surface.

[0068] Secondly, if Fig. 9 As shown in (b), the available liquid-gas interface area of ​​the composite membrane is larger than that of the original PVDF membrane, which means that the CNTs with a network structure loaded on the surface of the porous support layer increase the effective evaporation area of ​​water vapor during MD, thereby improving the water flux. However, excessive loading of CNTs will reduce the water flux of the composite membrane because the mass transfer resistance of water vapor increases with the increase of the thickness of the CNTs layer ( Fig. 9 (c)). In addition, if Fig. 9 As shown in (d) and (e), high thermal conductivity CNTs can also suppress the temperature polarization effect of the MD process and promote water evaporation.

[0069] Finally, the CNTs with a network structure loaded on the surface of the porous support layer significantly reduced the maximum pore size of the membrane ( Figure 5 ). LEP(LEP=-2βγ1cosθ / r max ) calculation formula shows that the LEP value is inversely proportional to the maximum pore size of the membrane, which means that a decrease in the maximum pore size (or pore radius) of the membrane will lead to an increase in the LEP value, thereby significantly improving its anti-wetting performance. Another important factor affecting wettability is the surface microstructure, among which the concave structure is crucial to maintaining a stable Cassie-Baxter wetting state for low surface tension liquids. Within the short contact time between the membrane surface and the SDBS droplet, all membranes can repel low surface tension liquids and exhibit a high contact angle ( Figure 7 (a)). However, when exposed to low surface tension liquids for a long time, only the PVDF@CNTs-PFOA membrane can maintain its anti-wetting properties ( Figure 7 (b)). However, the MD performance of the original PVDF membrane deteriorates rapidly when the surfactant concentration is greater than 1.0 mM, indicating that its surface is completely wetted (i.e., Wenzel state). Here, the network structure of the CNTs layer and the very low SA ( Figure 6(b)) endows the PVDF@CNTs-PFOA membrane surface with smooth properties. It can be expected that the perfluorinated CNTs layer with a network structure in this paper will effectively capture some air and build an additional barrier, which will greatly reduce the liquid-solid contact time and area, thereby promoting its excellent anti-wetting property.

Claims

1. A method for preparing a high-throughput and anti-wetting super-hydrophobic composite membrane for membrane distillation based on CNTs, characterized in that: The steps include: Step 1, obtaining a porous base membrane; Step 2, dispersing the carboxylated carbon nanotubes in a solution to obtain a suspension; Step 3, the suspension is filtered to load the carboxylated carbon nanotubes onto the surface of the porous base membrane, and after drying, fluorination is performed to obtain a super-hydrophobic composite membrane; The fluorination treatment process comprises: step a, preparing fluorine-containing polyamine; step b, immersing the porous base film loaded with carbon nanotubes in an activation reaction solution to activate the surface carboxyl groups, then adding the fluorine-containing polyamine to carry out a grafting reaction, and then washing and drying; The preparation of fluorinated polyamines is carried out by adding EDC•HCl, NHS and PFOA into an organic solvent, activating the organic solvent, and then adding EDA to react. The product is filtered and washed to obtain fluorinated polyamines. The reaction is carried out at 5-40°C for 10-30 hours. The molar ratio of EDC•HCl, NHS, PFOA and EDA added is 2:0.5-1.5:0.5-1.5:1-3; the organic solvent is ethanol; The activation reaction solution refers to an ethanol solution of EDC•HCl and NHS.

2. The method for preparing a high-throughput and anti-wetting super-hydrophobic composite membrane for membrane distillation based on CNTs according to claim 1, characterized in that: The concentrations of EDC•HCl, NHS and fluorinated polyamine in the activation reaction solution are 0.1-0.5 mol / L, 0.05-0.30 mol / L and 0.05-0.30 mol / L respectively; the grafting reaction is carried out at 5-40°C for 10-30 h.

3. The method for preparing a super-hydrophobic composite membrane for high-throughput and anti-wetting membrane distillation based on CNTs according to claim 1, characterized in that: The porous base membrane is a PVDF membrane, which is prepared by the VIPS method; the surface loading of carboxylated carbon nanotubes on the porous base membrane is 0.1-10 mg / cm 2 .

4. A super hydrophobic composite membrane for high-throughput and anti-wetting membrane distillation based on CNTs, characterized in that: The composite membrane is obtained by the preparation method according to any one of claims 1 to 3, wherein the composite membrane has a porous base membrane and a support layer supported on the surface of the porous base membrane, wherein the support layer is mainly composed of carboxyl carbon nanotubes, and the surface of the carboxyl carbon nanotubes is modified with perfluoropolyamine.

5. The super-hydrophobic composite membrane for high-throughput and anti-wetting membrane distillation based on CNTs according to claim 4, characterized in that: The superhydrophobic composite film has a water droplet contact angle of 130-170°.

6. Application of the super-hydrophobic composite membrane according to claim 4 in membrane distillation dehydration.